Digital media and children with Autism spectrum disorder - Pliska, Larissa (Technische Universität Dortmund, 2026)
In Germany, there are long waiting times for the diagnostic procedure of autism spectrum disorder (ASD), which creates uncertainty for the entire family and delays the start of family support and child therapy. This highlights the need for improved care for suspected cases of ASD. Digital technologies have the potential to support the screening and diagnostic processes for ASD. Therefore, this doctoral dissertation investigates the overarching research question: Can the digital screening tool, which has been developed by the IDEAS consortium, contribute to the detection of boys with ASD? Studies have often assumed that children with ASD are attracted to digital media, but this has not been investigated systematically. Accordingly, the media use of children with and without ASD was examined both in Study I and subsequently in Study II using a parent questionnaire. Study I included n = 15 parents of boys with ASD and n = 78 parents of typically developing (TD) boys. Study II included n = 117 parents of children with ASD and n = 58 parents of TD children. All children were between 6 and 11 years old. Mann-Whitney U-tests and Spearman correlations were used for the analyses. These studies indicate that children with ASD are familiar with and capable of using digital media, suggesting they are likely to accept and engage with digital screening tools. Study II also investigated parents' concerns about their children's media use, particularly regarding ASD symptoms. This investigation also included hierarchical regression models. In terms of developing a digital screening tool, it is essential that ASD symptoms can be observed in a digital setting. Study II indicates that parents were not concerned that their child's ASD symptoms would intensify. These results highlight the importance of examining whether ASD symptoms occur in a digital setting. Experimental Study III investigated the media equation of interaction between N = 20 boys with ASD, aged 6 to 11, using an equivalence test in a within-subject design. Study III indicates that children with ASD behave similarly in digital and real-life settings. This suggests that ASD symptoms can be detected in digital settings. Finally, Study IV examined whether digital screening tasks (emotion recognition and visual preference) could differentiate between children with and without ASD. The study included n = 24 boys with ASD and n = 24 TD boys, all between the ages of 6 and 11. Mixed logistic models were used for the emotion recognition task, mixed linear models for the visual preference task, and decision trees using the Gini index. Both the emotion recognition and visual preference tasks have an accuracy rate of 81.25%, and they should be considered together when making decisions. Overall, the results demonstrate that boys with ASD accept and are able to use a digital screening tool, that symptoms of ASD can be elicited in a digital setting, and that the tool can distinguish between boys with and without ASD. Therefore, the digital screening tool can contribute to the detection of boys with ASD. However, further optimization is needed to improve the early detection of ASD.
Media usage, parental concerns, and the potential for digital clinical screening
Keywords: Autism spectrum disorder; ASD; Digital media; Media usage; Parental concerns; Digital screening; 360; 370; Autismus; Neue Medien; Diagnostik